Identification and profiling of CXCR3–CXCR4 chemokine receptor heteromer complexes. (12th March 2013) - Watts, AO; van, MMH; Jaeger, WC; Seeber, RM; van, M; Vinet, J; van der, MMC; Siderius, M; Zaman, GJR; Boddeke, HWGM; Smit, MJ; Pfleger, KDG; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose The C‐X‐C chemokine receptors 3 (CXCR3) and C‐X‐C chemokine receptors 4 (CXCR4) are involved in various autoimmune diseases and cancers. Small antagonists have previously been shown to cross‐inhibit chemokine binding to CXCR4, CC chemokine receptors 2 (CCR2) and 5 (CCR5) heteromers. We investigated whether CXCR3 and CXCR4 can form heteromeric complexes and the binding characteristics of chemokines and small ligand compounds to these chemokine receptor heteromers. Experimental Approach CXCR3–CXCR4 heteromers were identified in HEK293T cells using co‐immunoprecipitation, time‐resolved fluorescence resonance energy transfer, saturation BRET and the GPCR‐heteromer identification technology (HIT) approach. Equilibrium competition binding and dissociation experiments were performed to detect negative binding cooperativity. Key Results We provide evidence that chemokine receptors CXCR3 and CXCR4 form heteromeric complexes in HEK293T cells. Chemokine binding was mutually exclusive on membranes co‐expressing CXCR3 and CXCR4 as revealed by equilibrium competition binding and dissociation experiments. The small CXCR3 agonist VUF10661 impaired binding of CXCL12 to CXCR4, whereas small antagonists were unable to cross‐inhibit chemokine binding to the other chemokine receptor. In contrast, negative binding cooperativity between CXCR3 and CXCR4 chemokines was not observed in intact cells. However, using the GPCR‐HIT approach, we have evidence for specific β‐arrestin2 recruitment to CXCR3‐CXCR4 heteromers in response to agonist stimulation. Conclusions and Implications This study indicates that heteromeric CXCR3–CXCR4 complexes may act as functional units in living cells, which potentially open up novel therapeutic opportunities.